A Rare Case of Encephalopathy in Children—Known but Unknown - Jain, Mukesh Kumar; Behera, Chinmaya Kumar; Panda, Sangram; Patnaik, Sibabratta; Sahoo, Bandya; Mishra, Reshmi; Behera, Jyoti Ranjan (Journal of Pediatric Neurology, 2022)
Metronidazole-induced encephalopathy is a rare cause of toxic encephalopathy in children. Although many cases have been reported in adults, it is rarely reported in the pediatric population. Here, we report a case of an 11-year-old boy who presented with acute-onset encephalopathy with slurring of speech after receiving metronidazole for treatment of acute gastroenteritis. Neuroimaging is the cornerstone in the diagnosis of this entity with typical involvement of cerebellum, brain stem, and splenium of the corpus callosum. In our case, magnetic resonance imaging of the brain revealed hyperintensity of the splenium of the corpus callosum on the fluid-attenuated inversion recovery sequence along with diffusion restriction in the diffusion-weighted imaging and apparent diffusion coefficient images. Rapid complete neurological and radiological recovery with supportive treatment is key in making the diagnosis. Although a safer and commonly used drug, new-onset encephalopathy after the use of metronidazole must be considered.
Keywords: metronidazole; encephalopathy; children; corpus callosum